Radiological and clinical outcome after operations in patients with congenital deficiencies of the wrist and hand - Schmelzer-Schmied, Nicole; Jung, Martin; Ludwig, Karl (European journal of radiology, 2011)
Purpose - To evaluate the incidence, therapy results, complications and radiologic workup of operatively treated congenital disorders of the hand and wrist in a large university center during a 10-year period. - Methods - The institutional database was retrospectively analysed for patients with congenital disorders of the hand and wrist treated operatively during a 10-year period (1998-2007). Disorders were classified according to Van Schoonhoven into 11 different entities. For each entity the incidence, the patients’ age at the time of operation, the pre- and postoperative clinical and radiological workup and the frequency of complications and reoperations were evaluated. - Results - A total of 278 patients was treated operatively for congenital disorders of the hand and wrist with syndactyly being present in 112, thumb hypoplasia in 15, polydactyly in 11, radial clubhand in 7, radioulnar synostosis in 6, clinodactyly in 6, thumb duplication in 6, brachydactyly in 4 and macrodactyly in 4 cases. Patients’ age at the time of operation varied substantially between the different entities with a mean age between 0.9 and 6.2 years. There were 9 complications (3%, n=278) - all of them infections. There were 28 reoperations (10%, n=278), 13 of them (5%, n=278) due to reoccurring webs in syndactyly. - Conclusion - Congenital disorders of the hand and wrist include various rare diseases with syndactyly and thumb hypoplasia being the most frequent entities. As a rule, diagnosis is obtained clinically. Radiologic workup typically consists of plain radiography. Complications are rare, whereas reoperations are frequent, mostly due to reoccurring webs in syndactyly.
Available online 17 November 2010
Gesehen am 12.10.2022